Scoping Review: Marketing Strategy of In Vitro Fertilization (IVF) - Prabandani, Dyah Ayu; Winarni, Sri; Arso, Septo Pawelas (International Journal Labs, 2023)
IVF or In Vitro Fertilization (IVF) is a new service program so to increase consumer or patient interest, a marketing strategy is needed that can increase the number of consumers themselves. This research uses the scoping review method to determine the marketing of test tube babies or IVF by formulating questions using the concepts P (Indonesia and Overseas), C (Marketing Strategy), and C (IVF). The results show that the promotion of In Vitro Fertilization (IVF) services is more efficient by using promotions on social media, distributing brochures, collaborating with ob-gyn doctors, and placing advertisements on websites related to IVF or IVF services. Promotion of IVF or IVF services is carried out to increase the number of users or patients who use these services. Several promotional media are considered capable of attracting customers to use IVF or IVF services, including promoting on social media, distributing brochures, collaborating with ob-gyn doctors, and placing advertisements related to IVF or IVF services on websites.